Can Ultrasound Performed in Prolonged Second Stage of Labor Predict the Difficulty and Success Rates of Operative Vaginal Delivery? - Gilboa, Y.; Moran, O.; Kivilevitch, Z.; Kees, S.; Borkowsky, T.; Achiron, R.; Weissmann-Brenner, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Objective: To evaluate different sonographic methods for the prediction of the difficulty and the success of operative vaginal delivery (OPD).Materials and Methods: A prospective study was performed on 45 term singleton uncomplicated pregnancies with prolonged 2nd stage of delivery with cephalic presentation. Measurements of the fetal head, relations between the fetal head and maternal pelvic parameters during rest and during maternal pushing were taken using translabial ultrasound.Results: 29 cases of OPD were successful and 4 cases failed ending in cesarean section. The passage of the biparietal diameter (BPD) of the infrapubic line (IPL) was statistically correlated with the success of OPD. Head station, passage of the BPD of the IPL, percentage of head after the IPL, circumference of head after IPL were all correlated with the difficulty of OPD. When the distance between the widest diameter of the head and the IPL is < 1.2 cm, there is a 90 % probability of success of OPD. When that distance is > 3.3 cm, there is 90 % probability of cesarean section. When the percentage of head beyond the IPL was > 54 %, there was 90 % probability of successful OPD.Discussion: Translabial ultrasound is useful in the prediction of the difficulty and the success of OPD. The higher the extent of head that passed the IPL, the less difficult the OPD and the greater the success rate of the OPD.
Keywords: translabial ultrasound; operative vaginal delivery; infrapubic line